# Simplify.Remove grouping symbols and combine like terms. A) `-4{3a^2-2[4a^2-(b+a^2)]}` B) -`2{x^2-3[x-(x-2x^2)]}`

### 1 Answer | Add Yours

To simplify, start at the inside expression going outside.

(A)

`-4{3a^2-2[4a^2-(b+a^2)]}`

Remove the parenthesis around b+a^2.

`=-4{3a^2-2[4a^2-b-a^2]}`

Combine like terms inside the bracket.

` `

`=-4{3a^2-2[3a^2-b]}`

Eliminate the bracket.

`=-4{3a^2-6a^2+2b}`

Combine like terms inside the braces.

`=-4{-3a^2+2b}`

And remove the braces.

`=12a^2-8b`

**Hence, `-4{3a^2-2[4a^2-(b+a^2)]}=12a^2-8b` .**

*(Note: For the second problem, please post it as separate question. )*